SIMULASI MODEL HBV PADA DAERAH ALIRAN SUNGAI BATANG ARAU PADANG - Sudiar, Nofi Yendri (Sainstek : Jurnal Sains dan Teknologi, 2015)
The objective of the study was to apply and to test the HBV subtropical model into a tropical region Batang Arau watershed Padang. Batang Arau watershed, located in Padang, covers an area of 106 km2. The HBV model was manually calibrated by trial adjustment of each parameter to obtain the appropriate physical characteristics of Batang Arau watershed. The study shows that the correlation coefficient of 0.48 and the value of NSE at 0.58. The value indicates the HBV modeling included in the category of accuracy being and indicated that HBV built models can not simulate the discharge of DAS Batang Arau quite well and can not be used to represent the real situation in DAS Batang Arau Padang. Although DAS Batang Padang Harau included in a small basin, but the model of HBV have not been able to describe the phenomenon that is properly due to the diversity of topography.Key words: Model HBV hydrology, watershed Batang Arau, the diversity of topography